Legal regulation of the subvention for the provision of state support to persons with special educational needs in Ukraine - Reva, V. (НДІ ПЗІР НАПрН України, 2023)
The article analyzes the legal regulation of the subvention for providing state support to persons with special educational needs in Ukraine. It is emphasized that when establishing the appropriate mechanism for providing such an inter-budgetary transfer, the legislator does not specify which levels of education are concerned and in which institutions such education can be obtained by persons with special educational needs (this refers to the form of ownership of a higher education institution, its organizational and legal form, etc.) We consider this approach constructive, as it ensures the principle of equality in the exercise of the right to education. It is emphasized that there is a legislative conflict regarding the range of persons who can be granted such a subvention. Thus, some legislative provisions refer to persons with special educational needs. At the same time, part 1 of Article 1033 at first refers to the provision of state support to persons with special educational needs, and then to children with relevant health problems. The author emphasizes that determining the circle of persons with special educational needs who can receive appropriate educational services at the expense of a subvention in this situation is fundamental. Based on the comparative legal analysis of the areas of use of the subvention funds for providing state support to persons with special educational needs, the author states that the areas of funding specified in the Budget Code of Ukraine differ from those specified in the Procedure for granting the said subvention. In particular, the Budget Code of Ukraine provides for such funding as remuneration of specialists on the basis of civil law contracts for the relevant classes or services. At the same time, the Procedure does not contain such provisions. It is quite logical that the Budget Code of Ukraine regulates the main provisions, and the relevant bylaws and regulations detail them. However, in our opinion, conceptually, these acts should correlate with each other. In this situation, on the contrary, this approach makes it impossible to adequately implement the procedure for granting the subvention under study. It is proposed to make appropriate amendments to the legal acts regulating the procedure for granting funds in the form of a subvention for providing state support to persons with special educational needs. У статті проаналізовано правове регулювання субвенції на надання державної підтримки особам з особливими освітніми потребами в Україні. Підкреслено, що, встановлюючи відповідний механізм надання такого міжбюджетного трансферту, законодавець не конкретизує, про які саме рівні освіти йдеться і в яких закладах таку освіту можуть здобувати особи з особливими освітніми потребами (йдеться про форму власності закладу вищої освіти, його організаційно-правову форму тощо). Вважаємо такий підхід конструктивним, оскільки він забезпечує принцип рівності у реалізації права на освіту. Наголошено на існуванні законодавчої колізії щодо визначення кола осіб, яким може бути надана така субвенція. Так, у деяких законодавчих положеннях йдеться про осіб з особливими освітніми потребами. Водночас у ч. 1 ст. 1033 Бюджетного кодексу України спочатку йдеться про надання державної підтримки особам з особливими освітніми потребами, а потім дітям з відповідними порушеннями здоров'я. Автор наголошує, що визначення кола осіб з особливими освітніми потребами, які можуть отримувати відповідні освітні послуги за рахунок субвенції, у цій ситуації є принциповим.На основі порівняльно-правового аналізу напрямів використання коштів субвенції на надання державної підтримки особам з особливими освітніми потребами констатовано, що напрями фінансування, визначені у Бюджетному кодексі України, відрізняються від тих, що визначені у Порядку надання зазначеної субвенції.Зокрема, Бюджетний кодекс України передбачає такий напрям фінансування, як оплата праці фахівців на підставі цивільно-правових договорів за проведення відповідних занять або надання послуг, однак Порядок не містить таких положень. Цілком логічно, що Бюджетний кодекс України регулює основні положення, а відповідні підзаконні нормативно-правові акти їх деталізують. Однак, на нашу думку, концептуально ці акти повинні корелювати між собою. У даній ситуації, навпаки, такий підхід унеможливлює належну реалізацію процедури надання досліджуваної субвенції. Пропонується внести відповідні зміни до нормативно-правових актів, що регулюють порядок надання коштів у вигляді субвенції на надання державної підтримки особам з особливими освітніми потребами.
Keywords: interbudgetary relations; interbudgetary transfers; subvention; state support; special educational needs; міжбюджетні відносини; міжбюджетні трансферти; субвенція; державна підтримка; особливі освітні потреби